Suppressing fatty acid synthase by type I interferon and chemical inhibitors as a broad spectrum anti-viral strategy against SARS-CoV-2 - Saba R. Aliyari; Amir Ali Ghaffari; Olivier Pernet; Kislay Parvatiyar; Yao Wang; Hoda Gerami; Ann-Jay Tong; Laurent Vergnes; Armin Takallou; Adel Zhang; Xiaochao Wei; Linda D. Chilin; et al. (Elsevier, 2022)
SARS-CoV-2 is an emerging viral pathogen and a major global public health challenge since December of 2019, with limited effective treatments throughout the pandemic. As part of the innate immune response to viral infection, type I interferons (IFN-I) trigger a signaling cascade that culminates in the activation of hundreds of genes, known as interferon stimulated genes (ISGs), that collectively foster an antiviral state. We report here the identification of a group of type I interferon suppressed genes, including fatty acid synthase (FASN), which are involved in lipid metabolism. Overexpression of FASN or the addition of its downstream product, palmitate, increased viral infection while knockout or knockdown of FASN reduced infection. More importantly, pharmacological inhibitors of FASN effectively blocked infections with a broad range of viruses, including SARS-CoV-2 and its variants of concern. Thus, our studies not only suggest that downregulation of metabolic genes may present an antiviral strategy by type I interferon, but they also introduce the potential for FASN inhibitors to have a therapeutic application in combating emerging infectious diseases such as COVID-19.